Local wheat peel as a solid surface to remove Azure B dye from aqueous solution:Equilibrium isotherms and thermodynamic study - Baghdad Science Journal (مجلة بغداد للعلوم, 2016)
In this research local wheat peel was used as an adsorbent surface for removal of Azure B (AB) dye from the aqueous solution. The adsorption process was performed at different experimental parameters, equilibrium time, temperature, ionic strength and solution pH. The isotherms of adsorption are of H-type as compared with Giles curves and the adsorption data were coincide with Freundlich equation. The adsorption kinetic data were analyzed using pseudo- first and second order kinetic models. The effect of temperature was studied and the amount of dye adsorbed was found to increase with the increasing of temperature from 25 to 50 oC. The values of thermodynamic functions like enthalpy and entropy have been estimated. The quantity of adsorbed dye on the wheat peel increase according to the sequence follows: pH 9.3? 8 ? 7 ?6 ?5.2.The adsorption phenomenon is influenced by the sodium chloride concentration of solution. The obtained data refer to a decrease in amount of Azure B adsorbed in the existence of electrolyte.